Antimicrobial properties of the skin secretions of frogs - Thashlin Govender; Abeda Dawood; Adriaan Esterhuyse; David Katerere (South African Journal of Science)
Antimicrobial resistance results in increased morbidity and mortality, and increased health-care costs. Therefore the need to develop new classes of antibiotics is indispensable. Antimicrobial peptides are a relatively new class of potential antibiotics which are fast acting, possess broad-spectrum activity and are able to escape many of the currently known mechanisms of drug resistance. They have been shown to be active against Gram-negative and Gram-positive bacteria, fungi, enveloped viruses and even cancer cells. However, toxicity to healthy host cells remains a concern and has affected the clinical development of therapeutics based on antimicrobial peptides. The purpose of this review is to discuss recent advances in research focused on antimicrobial peptides from frogs and the challenges in conducting research in this area in southern Africa. An extensive literature review of relevant articles published between 1980 and the present was conducted using PubMed, ScienceDirect, Sabinet, Elsevier and GoogleScholar. There has been little research done on anurans from southern Africa which are endemic to the region, and there is therefore a need to focus on this group for the purposes of bioprospecting for potentially new antimicrobial peptide compounds.